Moralidad, empatía, inteligencia emocional y liderazgo transformacional: un modelo de rutas en estudiantes de posgrados gerenciales en una universidad venezolana (2013)
A path analysis model was contrasted to establish causal relationships between the level of post-conventional moral development, empathic concern as a measure of empathy, emotional self-awareness and emotional self-regulation on transformational leadership style. The study sample was made up of graduate students in management of a public Venezuelan University and was composed of professionals of both sexes from different disciplinary fields (N = 162, mean age = 31,37, SD = 4,67). The instruments used among others, were the Defining Issues Test (DIT), the Interpersonal Reactivity Index (IRI) and the Sub-Scale of Empathic Understanding. Results show that the proposed model was partially valid; this indicates that the understanding of the relationships between the model variables is more complex than what is proposed in the literature; in this regard, empathy is the most influential variable in the model. As a matter of fact, there are high and significant direct effects on post-conventional moral development and the self-knowledge and emotional self-control ability.Keywords: moral development, empathy, emotional intelligence, leadership styles, path analysis.